2019
DOI: 10.1002/jcla.23038
|View full text |Cite
|
Sign up to set email alerts
|

Enhance the effectiveness of clinical laboratory critical values initiative notification by implementing a closed‐loop system: A five‐year retrospective observational study

Abstract: Background Accurate and timely clinical laboratory critical values notification are crucial steps in supporting effective clinical decision making, thereby improving patient safety. Methods A closed‐loop laboratory critical value notification system was developed by a multidisciplinary team of clinicians, laboratorians, administrators, and information technology experts. All the laboratory critical values that occurred at Beijing Tsinghua Changgung Hospital (BTCH, Beijing, China) from 2015 to 2019 were analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 27 publications
(53 reference statements)
1
20
0
Order By: Relevance
“…10,11c The difference is we only analyze the laboratory test result from the inpatient ward which has a higher chance to contribute to critical value, whereas the previous study involved the emergency and outpatient departments. 10,6 For the example low platelet count ≤100.000/μL (thrombocytopenia) and increasing hematocrit >20% are the laboratory criteria for hospitalization on DHF cases with clinical symptoms which prone to get critical value in inpatient ward. 14 The hospital target about laboratory critical value reporting yet achieved as they established the target is 100%.…”
Section: Resultsmentioning
confidence: 99%
“…10,11c The difference is we only analyze the laboratory test result from the inpatient ward which has a higher chance to contribute to critical value, whereas the previous study involved the emergency and outpatient departments. 10,6 For the example low platelet count ≤100.000/μL (thrombocytopenia) and increasing hematocrit >20% are the laboratory criteria for hospitalization on DHF cases with clinical symptoms which prone to get critical value in inpatient ward. 14 The hospital target about laboratory critical value reporting yet achieved as they established the target is 100%.…”
Section: Resultsmentioning
confidence: 99%
“…Patient safety is a continuous focus for the joint commission and thus for our laboratory also. 15 The median reporting time of notification to the ICU, emergency, and other inpatient areas was also reduced significantly ( Table 2 ) but communicating the critical value to outpatients and their timely intervention by the responsible care giver is still a major hurdle ( Table 2 ). Li et al had also reported that quality indicators for critical alerts were poor for outpatient setting.…”
Section: Discussionmentioning
confidence: 99%
“…There communication of critical values as essential [14], and our respondents seem to agree. Notification is usually ineffective when contacting the responsible physician by telephone [15]. Telephone notification has advantages according to AlSadah et al [8], such as affording the opportunity to read back the results with immediate explanation, if needed, to minimise errors.…”
Section: Correct Answers Of Upper and Lower Limits And Units Of Criti...mentioning
confidence: 99%
“…Past studies co-ordinated our current results and showed the attitude towards the policies and guidelines regarding critical value notification. Managing the notification time and following a flowchart to report critical values can reduce reporting errors, improve notification of critical values and further guarantee patient safety [15]. Dixon et al [29] stated that result notification should be available in health departments within 1440 to 2880 min.…”
Section: Correct Answers Of Upper and Lower Limits And Units Of Criti...mentioning
confidence: 99%